PENGGARUH PENGGUNAAN GAME QUIZIZZ TERHADAP HASIL BELAJAR PADA MATA PELAJARAN MATEMATIKA KELAS V SDK ST. YOSEPH 4 NAIKOTEN KUPANG - Maria M.Elu Feka; Roswita Lioba Nahak; Yulsy M. Nitte (STKIP Subang, 2026)
The Effect of Using the Quizizz Game on Learning Outcomes in Mathematics Subject of Grade V Students at SDK St. Yoseph 4 Naikoten, Kupang City. Undergraduate Thesis, Elementary School Teacher Education Study Program, Faculty of Teacher Training and Education, Citra Bangsa University. Advisors: Roswita Lioba Nahak, S.Pd., M.Pd. & Yulsy Maselina Nitte, SH., M.Pd. Mathematics learning in elementary schools often faces several problems, such as students’ low interest in learning mathematics, the perception that mathematics is a difficult and boring subject, and students’ lack of focus during lessons. Moreover, when teachers ask about material taught in previous meetings, only a small portion of students are able to recall it well. The limited use of learning media, with teachers relying mainly on textbooks as the primary source, also contributes to students’ low understanding of mathematical concepts. This study aims to examine the effect of using the Quizizz game on mathematics learning outcomes of fifth-grade students at SDK St. Yoseph 4 Naikoten, Kupang City. This research employed a quantitative approach with a quasi-experimental method, specifically using a non-equivalent control group pretest–posttest design. The sample consisted of 30 fifth-grade students. Research instruments included tests and documentation studies. Data analysis techniques involved normality test, homogeneity test, hypothesis testing, and paired sample t-test. The results showed an increase in the average learning outcome scores from the pretest (67.67) to the posttest (77.67). The paired sample t-test results indicated a significant difference between pretest and posttest scores (sig. 0.000 < 0.05) with a very strong correlation (r = 0.934). In conclusion, the use of the Quizizz game has a positive and significant effect on the mathematics learning outcomes of fifth-grade students at SDK St. Yoseph 4 Naikoten, Kupang City.